VS-split load balancing algorithm in DHT-based P2P systems - Lei YANG; Ren-fa LI; Shi LIU; Zhi-xing CHEN; Ken-li LI (Tongxin xuebao, 2013)
The method using virtual servers for balancing the load in DHT-Based P2P systems was studied.The load distribution in DHT-based overlay network using virtual servers were modeled,the occurrence probability of single vir-tual server problem (SVSP) was analyzed and computed in details,and a novel VS-split load balancing algorithm (VSSLBA) was proposed to deal with the SVSP by splitting virtual server into small ones.Simulations verify the cor-rectness of probability analysis and the performance of VSSLBA.